The Swedish riding school: a social arena for young riders. Issue 9 (2nd September 2018) - Thorell, Gabriella; Augustsson, Christian; Stråhlman, Owe; Morgan, Karin
Abstract: The aim was to explore how young riders experience the riding school. By analysing focus groups interviews, a picture emerged showing that young riders' main motive for participating at riding schools was the social aspects. Riding schools could be characterized through an institutional perspective in which the young riders became internalized and socialized into a stable culture. The young riders identified with the norms and values of the riding instructors through master–apprentice learning. In addition, the results revealed a change in the stable culture since the instructors encouraged social interactions and participation in the community that became central to learning and development. Opportunities to influence and interact were important for the individuals and from a child's rights perspective. Through participation in the community of practice at riding schools, young riders not only learn about riding and horse management but also develop important personal social skills.